SHARIA IN PUBLIC SPACE: COMMUNICATION MODELS IN THE ADOPTION OF ISLAMIC SHARIA IN URBAN MUSLIM SOCIETY IN LANGSA, ACEH - Zulkarnain Zulkarnain; Sharifah Nadiah Syed Mukhiar; Muhajir Muhajir; Al Mutia Gandhi; Syiva Fitria (Akademika : Jurnal Pemikiran Islam, 2023)
The application of Islamic law in Langsa City is currently still reaping the pros and cons, until now the application of Islamic law is not going well. Good communication is needed between the government and the people of Aceh to build harmony in the application of Islamic law. This article aims to analyze the communication model built by the Langsa City government for the Urban Muslim Society to socialize the implementation of Islamic law. This paper is generated from empirical research with a qualitative approach, the main data obtained from in-depth interviews with parties directly involved in policy-making and implementing Islamic law in Langsa City. The results of the study show that there are several communication models built by the Langsa City government in the application of Islamic law, including; First, the interpersonal communication model that focuses on a personal approach, so that the message that reaches the community is more concrete and there is no miscommunication; second, the mass communication model that focuses on the pattern of delivering messages through several media such as social media and print media. The use of social media and print media is very useful in disseminating Islamic law, although, on the one hand, the mass communication model carried out by the Langsa City government is not able to reach remote areas that cannot access information technology. The communication model is carried out as a form of government authority in the enforcement of Islamic law in Langsa City because when religion enters the state system, the implementing authority belongs to the government.